Chinese EFL learners’ processing of English binomials: the role of interlexical and intralexical factors - Chen, Zhuo; Fang, Nan (Frontiers in Psychology, 2024)
Binomials have been relatively understudied compared to other types of multiword expressions (MWEs) in second language research, such as collocations and idioms. This study investigated English as a Foreign Language (EFL) learners’ processing of English binomials and how it is influenced by interlexical factors (L1-L2 congruency and L1-lexicalization) and intralexical factors (word and binomial frequency, binomial reversibility, and binomial predictability). Forty Chinese EFL learners participated in a phrase acceptability judgment task of 64 target binomials (16 congruent L1-lexicalized, 16 congruent L1-nonlexicalized, and 32 incongruent) and 64 non-binomial controls. Results revealed that learners experienced difficulty judging the formulaicity of binomials. They processed binomial stimuli significantly faster than non-binomial baselines, demonstrating a binomial phrase effect. They also processed L1-L2 congruent items faster and more accurately than incongruent items, showing a robust congruency effect. The congruent items which are lexicalized in the L1 showed further processing advantage than the non-lexicalized items, indicating a graded congruency effect. Moreover, binomial reversibility and binomial predictability (measured with cloze probability) also showed significant effects. These findings highlight the need to distinguish and investigate different types of congruency, explore appropriate measures for MWE predictability, and to examine binomials focusing on their unique features.